2019
DOI: 10.2147/dmso.s230061
|View full text |Cite
|
Sign up to set email alerts
|

<p>Type 2 Diabetes-Associated Genetic Polymorphisms as Potential Disease Predictors</p>

Abstract: Diabetes is a major cause of mortality worldwide. There are several types of diabetes, with type 2 diabetes mellitus (T2DM) being the most common. Many factors, including environmental and genetic factors, are involved in the etiology of the disease. Numerous studies have reported the role of genetic polymorphisms in the initiation and development of T2DM. While genome-wide association studies have identified around more than 200 susceptibility loci, it remains unclear whether these loci are correlated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 212 publications
(212 reference statements)
1
26
0
Order By: Relevance
“…17 The genome-wide association studies (GWAS) for obesity detected strong association between the fat massand obesity-associated gene (FTO) with higher body mass index (BMI) and metabolically unhealthy state in individuals. 18,19 At FTO-rs9939609 SNP, carriers of risk genotype (AA) have a 2.02-fold higher risk for obesity and 1.17-fold higher risk for metabolic syndrome compared with non-risk genotype carriers. 20,21 However, in several studies, the association FTO with metabolic traits was entirely explained by the association with obesity.…”
Section: Introductionmentioning
confidence: 99%
“…17 The genome-wide association studies (GWAS) for obesity detected strong association between the fat massand obesity-associated gene (FTO) with higher body mass index (BMI) and metabolically unhealthy state in individuals. 18,19 At FTO-rs9939609 SNP, carriers of risk genotype (AA) have a 2.02-fold higher risk for obesity and 1.17-fold higher risk for metabolic syndrome compared with non-risk genotype carriers. 20,21 However, in several studies, the association FTO with metabolic traits was entirely explained by the association with obesity.…”
Section: Introductionmentioning
confidence: 99%
“…A fundamental genetic heterogeneity has been found in T2DM ( Mannino et al, 2019 ). Genome Wide Association Studies (GWAS) focused on the genetic heterogeneity have discovered a number of loci, KLF14, KCNQ1, DUSP9, FTO, HNF4A, IGFBP2, CDKN2A/B, TCF7L2, KCNJ11, antioxidant genes, DNAJC3, PGC-1α, ADIPOQ, CDKAL1, POMC, PPARγ2, and SLC30A8 , that could be potential predictors of the disease ( Cho et al, 2019 ; Witka et al, 2019 ). One among the loci, in particular, CDK5 regulatory subunit associated protein 1-like 1, cdkal1 , is intriguing as a locus remote from the insulin gene, and a tRNA modification enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…We focus on the Pro12Ala polymorphism of the peroxisome proliferator‐activated receptor γ2 (PPARγ2) gene. This is one the best‐replicated genetic risk factor for T2D 9 . PPARγ2 encodes for a transcription factors that belong to the family of nuclear receptors; it regulates several genes involved in carbohydrates and lipids metabolism, promotes adipocytes differentiation and fatty acids uptake and modulates insulin sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…PPARγ2 encodes for a transcription factors that belong to the family of nuclear receptors; it regulates several genes involved in carbohydrates and lipids metabolism, promotes adipocytes differentiation and fatty acids uptake and modulates insulin sensitivity. Multiple studies have reproducibly shown that the common Pro12Ala polymorphism is associated with greater insulin sensitivity and protection from development of T2D in the general population 9 . Apparently at variance with this evidence, prospective studies in people with disglycaemia have shown that the Ala12 variant is associated with a greater risk of transition from impaired glucose tolerance to diabetes 10‐12 .…”
Section: Introductionmentioning
confidence: 99%